Central nervous system involvement by mantle cell lymphoma. Issue 2 (28th January 2023) - McLaughlin, Nicole; Wang, Yucai; Witzig, Thomas; Villasboas, Jose; Habermann, Thomas; Inwards, David; Bennani, Nora; Thanarajasingam, Gita; Nowakowski, Grzegorz; Porrata, Luis; Thompson, Carrie; Micallef, Ivana; et al.
Abstract: Involvement of the central nervous system (CNS) is a rare complication of mantle cell lymphoma (MCL) with limited treatment options. We report the outcomes of 36 patients with CNS involvement compared to 72 matched control MCL patients without CNS involvement. Four patients (11%) with CNS MCL were diagnosed with CNS involvement at time of MCL diagnosis. Median OS from MCL diagnosis was 50.3 months (95% CI: 22.8–79.6) for the CNS MCL group compared to 97.1 months (95% CI: 82.8–NR; p = <0.001) for the control group. Median OS from CNS involvement was 4.7 months (95% CI: 2.3–6.7). CNS involvement by MCL has dismal outcomes as evident by a short median OS and PFS after CNS involvement. Advanced stage, blastoid variant, elevated LDH, and elevated Ki67 at MCL diagnosis were features more commonly seen in the CNS MCL cohort.